Service Quality Higher Education and Customer Satisfaction Among Undergraduate Students of the University of Jordan - Alnaser, Ahmad Salih Mheidi (2010)
This study attempts to examine the relationship between service quality dimensions and overall service quality (tangibility, responsiveness, reliability, assurance and empathy) and students satisfaction. Data were collected through distributing 185 questionnaires among undergraduate students in a faculty of business at University of Jordan. The finding of this study showed that the assurance and the reliability dimensions of service quality are the two most important dimensions and have significant positive relationship with knowledge sharing.